Searching water megamasers by using mid-infrared spectroscopy (I): Possible mid-infrared indicators. Issue 4 (22nd July 2021) - Lam, Man I; Walcher, C Jakob; Gao, Feng; Yang, Ming; Li, Huan; Hao, Lei
ABSTRACT: Water megamasers at 22 GHz with a gas disc configuration in galaxies provide the most precise measurements of supermassive black hole masses, as well as independent constraints on the Hubble constant in the nearby universe. The existence of other maser types, such as jet or outflow masers, represents another tracer for AGN science. However, the detection rate of water megamasers in galaxies is extremely low. Over 40 yr, only ∼ 160 galaxies are found to harbour maser emission, and ∼30 per cent of them show features in their maser emission that indicate a disc-like geometry. Therefore, increasing the detection rate of masers is a crucial task to allow expanding on maser studies. We present a comparison of mid-infrared spectroscopic data between a maser galaxy sample and a Seyfert 2 control sample. We find that maser galaxies show significant peculiarities in their mid-infrared spectra: (1) Maser galaxies tend to present stronger silicate absorption at τ9.7 μ m than the control sample, (2) PAH 11.3 μ m emission in maser galaxies is much weaker than in the control sample, (3) spectral indices at 20–30 μ m are steeper in maser galaxies than in the control sample and tend to be mid-infrared enhanced population. We conclude that there may be good indicators in mid-infrared and far-infrared which could differentiate maser and non-maser Seyfert 2 galaxies. Upcoming infrared facilities, such as the James Webb Space Telescope, may be able to exploit these and other useful criteria and tracers for water megamaser observations.